Critical thinking : an appeal to reason - Tittle, Peg, 1957- (Routledge, 2011)
In Critical Thinking: An Appeal to Reason, Peg Tittle empowers students with a solid grounding in the lifelong skills of considered analysis and argumentation - skills that should underpin every student's education. Starting with the building blocks of a good argument rather than with the pitfalls to avoid, this comprehensive new textbook offers a full course in critical thinking.€ It includes chapters on the nature and structure of argument, the role of relevance, truth and generalizations, and the subtleties of verbal and visual language. Throughout the text there are numerous sample ar.